Use of macro doses of oxytocin in women with stillbirth - Hernández González, Ana Marcela; Jiménez Calderón, Fabiana (Nursing Journal in Costa Rica, 2017)
The objective of this study was to analyze the best available scientific evidence on the use of macro doses of oxytocin compared to standard doses in women who presented fetal death in the year 2017. The professional obstetric actions for delivery care vary widely among the different countries, between the different national institutions and the different teams responsible for such care. Conducting research in the field of obstetrics allows us to determine what are the best actions based on scientific evidence and thus provide quality care to the pregnant user.In order to carry out the study, the methodology of Clinical Practice Based on Evidence was applied; It began with the elaboration of the clinical question followed by the search of information in the scientific databases such as MEDLINE, COCHRANE, SCIENCIE DIRECT, TRIPDATA BASE, SCIELO and PUBMED. The search in all the databases retrieved a total of 2 548 articles, which were carefully reviewed by title and abstract. At the end, an article was retrieved which was the subject of critical analysis. It is concluded that the best available evidence is insufficient to give a reliable answer to the clinical question established on the subject.